Knowledge, attitude and practice of invasive mechanical ventilation protocolized weaning among ICU nurses and its influencing factors: A cross-sectional study - Li Wang; Yating Yu; Yan Zhu; Qin Zhang; Lei Sun; Juan Chen; Li Xiao; Ping Jia (PLoS ONE, 2026)
Background Many foreign countries have implemented protocolized weaning led by respiratory therapists (RTs) or nurses, which can reduce the duration of mechanical ventilation. At present, the implementation of ventilator weaning in China is led mainly by doctors. Objective To investigate the status quo of the knowledge, attitudes and practices of adult intensive care unit (ICU) nurses in tertiary hospitals concerning invasive mechanical ventilation (IMV) protocolized weaning and to analyze its influencing factors. Methods This cross-sectional study was conducted from September to November 2023 in 30 tertiary hospitals in Sichuan, Chongqing, and Nanjing, and included a total of 700 nurses. Data were collected using a questionnaire designed by the research team. The questionnaire consisted of 39 items, including 3 dimensions: knowledge (concepts and precautions of protocolized weaning, weaning screening and spontaneous breathing trial (SBT) evaluation, SBT methods, extubation knowledge), attitude (professional perceptions, personal beliefs, learning willingness) and practice (implementation of weaning screening assessment and SBT, implementation of extubation). Data analysis was performed using IBM SPSS Statistics, version 25. Univariate analysis was performed using a t test or analysis of variance, while multifactor analysis was conducted using multiple linear regression analysis. Results A total of 700 questionnaires were recovered, and after the exclusion of invalid questionnaires, 643 valid responses remained. Among the 643 nurses, 65.47% were from the general intensive care unit (GICU), 86.00% of nurses’ ICU weaning were led by doctors, 43.08% of nurses did not participate in the knowledge of weaning training after work, and 94.56% expressed their willingness to participate in the training of protocolized weaning. The total standardized score of the knowledge, attitudes and practices related to the protocolized weaning of ICU nurses was 82.70 ± 10.69 points, and the standard scores for the dimensions of knowledge, attitudes, and practices were 78.50 ± 16.67, 87.96 ± 10.76, and 76.53 ± 15.51, respectively. Pearson correlation analysis revealed that the correlation coefficients between knowledge and attitude, knowledge and practice, and attitude and practice were 0.274, 0.325, and 0.491, respectively, which were significantly positive correlations ( P < 0.01). The employment form, whether the ICU has a protocolized weaning program, whether the nurse is willing to participate in the protocolized weaning training, ICU type, and the position were the main factors influencing the ICU nurses’ IMV-protocolized weaning knowledge scores ( P < 0.05). The professional title, ICU type, whether the ICU has a protocolized weaning program, the role of nurses in weaning decision-making, and whether the nurse is willing to participate in the protocolized weaning training were the main factors influencing ICU nurses’ IMV protocolized weaning attitude score ( P < 0.05). Gender, ICU type, the position, whether the ICU has a protocolized weaning program, the role of nurses in weaning decision-making, the number of weaning training times in the past 3 years, and whether the nurse is willing to participate in the protocolized weaning training, were the main factors influencing ICU nurses’ IMV-protocolized weaning practice score ( P < 0.05). Conclusion The study found that the participants’ knowledge and practice of the protocolized weaning from IMV were at a moderate level, but they had a more positive attitude. Most participants were willing to participate in the protocolized weaning training. The development of a protocolized weaning program and the provision of related training can promote nurses’ understanding of weaning and increase their willingness to participate in weaning.